2010
DOI: 10.18632/oncotarget.198
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an Actinomycin D/VX-680 aurora kinase inhibitor combination in p53-based cyclotherapy

Abstract: AbstrAct:p53-based cyclotherapy is proving to be a promising approach to palliate undesired effects of chemotherapy in patients with tumours carrying p53 mutations. For example, pre-treatment of cell cultures with Nutlin-3, a highly-selective inhibitor of the p53-mdm2 interaction, has been successfully used as a cytostatic agent to protect normal cells, but not p53-defective cells, from subsequent treatment with mitotic poisons or S-phase specific drugs. Here we sought to evaluate whether low doses of Actinomy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(14 citation statements)
references
References 25 publications
4
10
0
Order By: Relevance
“…S2). These observations, which extend our previous work using LDactD in combination with the Aurora kinase inhibitor VX680, 6 suggest that the performance of nutlin-3 and LDactD in cyclotherapy is comparable. However, Figure 6 shows that, unlike nutlin-3, LDactD shields HCT116-p53ko cells from the cytotoxicity caused by Ara-C and vinca alkaloids.…”
Section: Methodssupporting
confidence: 86%
See 3 more Smart Citations
“…S2). These observations, which extend our previous work using LDactD in combination with the Aurora kinase inhibitor VX680, 6 suggest that the performance of nutlin-3 and LDactD in cyclotherapy is comparable. However, Figure 6 shows that, unlike nutlin-3, LDactD shields HCT116-p53ko cells from the cytotoxicity caused by Ara-C and vinca alkaloids.…”
Section: Methodssupporting
confidence: 86%
“…30 It has been shown that human epidermal keratinocytes undergo reversible cell cycle arrest when exposed to 1 nM ActD for 24 h. 30 Similarly, HNDFs incubated with 4 nM ActD for 72 h re-entered the cell cycle when cultivated further in fresh medium. 6 In agreement with these observations, Figure 2A shows that HNDFs accumulate in G 1 and G 2 in response to LDactD, while Figure 2B confirms the reversibility of the cell cycle arrest.…”
Section: Tenovin-6 Leptomycin B Nutlin-3 and Low-dose Actinomycin Dsupporting
confidence: 83%
See 2 more Smart Citations
“…Inhibition of HDM2 by a wide range of antagonists has been shown to lead to increased cellular levels of wild type p53 and cell death [2023]. In normal cells, HDM2 inhibition can cause reversible arrest, highlighting a possible target for cyclotherapy regimens [2426]. The prototypical HDM2 antagonist Nutlin and its numerous derivatives comprise a signature chemotope that recapitulates the interaction of 3 key residues in the N-terminal region of p53 (F19, W23, L26) with a hydrophobic pocket in the N-terminal domain of HDM2 [20, 2729].…”
Section: Introductionmentioning
confidence: 99%